Strategi Manajemen Penanggulangan Pandemi Covid-19 Pada Kegiatan Pengeboran Lepas Pantai PT.COSL INDO - Asep Hermawan Sanudin; Bernard Hasibuan; Sugiarto Sugiarto (LPPM Universitas Respati Indonesia, 2022)
Thesis title is ‘’Management strategy and handling COVID-19 in oil and gas offshore drilling activity PT.COSL INDO.’’. Research Methodology by using qualitative and quantative. An interview were conducted to key person’s (Offshore Installation Manager, Offshore Installation Superintendent, HSE Advisor, Company man from PERTAMINA & doctor on duty) at Drilling Rig Asian Endevour 1 of PT.COSL INDO. To obtain the best strategy by using SWOT analysis and QSPM matrix analysis to determine which strategy is more applicable and proper. Whereas, to measure how staff’s perception about COVID-19 policy by distributed questionnaires to 77 workers. HIRARC method also utilized to identify hazard in some activity which may contribute in spreading COVID-19 as well as control measure implemented to mitigate the risks. The results of study comprises of: Rig AE1 PT.COSL INDO using client Standing Order and Corporate MERP to handle and to control of COVID-19, Key Person applied Collaborative strategy with its Subcontractors as well as Crewing Management to recruit local staff in lieu of expatriate and at least 12 activities most common frequent which found as potential virus contamination.